Giordano Bruno : os poderes da religião e do estado na (contra) produção do conhecimento - Paixão, Grace Cristina Milet Castro da (2017)
This research consists on a discursive analysis of the filmic materiality "Giordano Bruno" (1973), directed by Giulliano Montaldo. With the contemplation of this cinematographic film, we seek to understand the productions of meaning, in line with Discourse Analysis (French line), for which language, as a socio-historical object, produces effects of meanings, according to the postulates of Mussalim (2001 ), Orlandi (1984, 2002, 2012). Aside from this theoretical contribution, we look at the relations of power / knowledge, truth, discipline control, and vigilance, according to Foucauldian theories (1987, 1988, 1999, 2009, 2011, 2012, 2015). From this theoretical device, we analyzed discursively the film, verbal and nonverbal language, problematizing the relations of power / knowledge in the construction of truths. We also examined the relationships between the characters, the environment, the set design, reflecting on the production of meaning, from the objects, the scenes. In order to contextualize the cinema in the socioeconomic context in which it emerged, we studied the cultural industry, according to the teachings of Teixeira Coelho (1980). Regarding the questions about the formation of a value system in the film media, we used the Bernadet research (1985), Charaudeau (2007), Kristeva (2007), Martin (2011). As the methodological aspects, we related the theoretical and analytical devices, using Orlandi's (1984) proposal, according to which it is possible to delimit our object by making discursive cuts (RD), which consist of fragments of a discursive situation, in which correlate language and situation. In this sense, we made three cutouts on the discursive whole: the discourse of / on knowledge; the discourse of / on the power of surveillance; the discourse of / about the body tortured (the images constructed from the relation power / knowledge). From these cutouts, we analyzed some discursive sequences (SD), in order to relate the analytical devices to the theoretical devices. Because our object and the theories that sustain it, we consider our work with a qualitative character. As a result of our analysis, we verify which sense effects the discursive gestures promote. In this direction, we believe that this research becomes relevant insofar as, according to the observation of the power / knowledge / truth / subjectivity relations, in this filmic materiality, we return to the history of the teacher's constitution, from the position of the philosopher, in the history of knowledge. In this sense, according to Foucault (1997), we try to "eventalize" history, seeking the singularity, the rarity, the games of strength, searching for the signification of the concepts of time, space, according to the idea of infinity defended by the protagonist, Giordano Bruno.